The impostor phenomenon among doctoral students: a scoping review - Wang, Yanyan; Li, Wanhe (Frontiers in Psychology, 2023)
Emerging evidence suggests that the Impostor Phenomenon (IP) among doctoral students is a serious problem worldwide academic. Although previous studies demonstrate that IP can endanger doctoral students' academic advancement and psychological well-being, limited studies systematically and comprehensively explore the IP among those population. Thus, the fundamental goal of this study is to conduct a scoping review of IP among doctoral students so as to clarify the reality of their situation. Systematic searches were conducted using 5 databases: Springer, Google Scholar, Web of Science, PubMed, and JSTOR for empirical studies published from 1978 to 2023. Two reviewers independently carried out the literature search, study selection, data extraction and assessment of study; disagreements were resolved by a third reviewer. 30 empirical studies covering four specific domains were include in current research, including the characteristics of IP among doctoral students, factors contributing to IP among doctoral students, correlation of IP with doctoral students' mental illness, and measurement of IP. The findings of this study may provide insight to improving the comprehension of IP among doctoral students and establishing the groundwork for future research in this field.